Comparative analysis of the fatty acid composition of raw material of rye (Khamarka variety) and barley (Shedevr variety) of Ukrainian selection - Ganna Tartynska (PC Technology Center, 2021)
Introduction. Sowing rye (Secale cereale L.) and common barley (Hordéum vulgáre L.) are annual herbaceous plants of the Poaceae family, they are widely cultivated in many countries around the world as cereals and fodder crops. Sufficient raw material base of sowing rye and barley makes them promising sources for new drugs.